Comparison of total body irradiation-based or non-total body irradiation-based conditioning regimens for allogeneic stem cell transplantation in pediatric leukemia patients - Sang Jeong Kim; Dong Kyun Han; Hee Jo Baek; Dong Yeon Kim; Taek Keun Nam; Tai Ju Hwang; Hoon Kook (Korean Pediatric Society, 2010)
Purpose : This study aims to compare the outcome of total body irradiation (TBI)- or non-TBI-containing conditioning regimens for leukemia in children. Methods : We retrospectively evaluated 77 children conditioned with TBI (n=40) or non-TBI (n=37) regimens, transplanted at Chonnam National University Hospital between January 1996 and December 2007. The type of transplantation, disease status at the time of transplant, conditioning regimen, engraftment kinetics, development of graft-versus-host disease (GVHD), complications, cause of deaths, overall survival (OS), and event-free survival (EFS) were compared between the 2 groups. Results : Among 34 patients with acute lymphoblastic leukemia (ALL), 28 (82.4%) were in the TBI group, while 72.7% (24/33) of patients with myeloid leukemia were in the non-TBI group. Although the 5-year EFS of the 2 groups was similar for all patients (62% vs 63%), the TBI group showed a better 5-year EFS than the non-TBI group when only ALL patients were analyzed (65% vs 17%; P =0.005). In acute myelogenous leukemia patients, the non-TBI group had better survival tendency (73% vs 38%; P=0.089). The incidence of GVHD, engraftment, survival, cause of death, and late complications was not different between the 2 groups. Conclusion : The TBI and non-TBI groups showed comparable results, but the TBI group showed a significantly higher 5-year EFS than the non-TBI group in ALL patients. Further prospective, randomized controlled studies involving larger number of patients are needed to assess the late-onset complications and to compare the socioeconomic quality of life.